WORKLOADS OF YOUNG SOCCER PLAYERS - Pilis, Karol; Stec, Krzysztof; Witkowski, Zbigniew; Stanula, Arkadiusz; Gabrys, Tomasz; Mikołajec, Kazimierz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The purpose of this study is to present a comparison of the workload demonstrated by young soccer players during the phases of warm-up (WU), first half (FH) and second half (SH) of a league match. Eleven young Polish soccer players took part in this research, playing a league match after completing the WU. During the WU, FH and SH of the match the following variables were recorded: total distance run, maximal and average speed achieved during the runs, number of sprints, distances run in the different speed zones, durations of increased heart rate (HR) in specific ranges, and the maximal, mean and minimal HR. The variables were recorded by means of the Global Positioning System (GPS). The research showed that there were significant differences between the WU, FH and SH in the total distances run (F=30.107, p<0.001), the average speed achieved during the runs (F=37.731, p<0.001), the distances run at different speeds (p<0.001), the duration of increased HR in specific zones, and HRmean (p=0.002) and HRmin (p<0.001). Post hoc analysis confirmed that, for the majority of the analyzed parameters, the WU provided a smaller load for the body than did the FH or SH, the intensity of which in some part was higher than that encountered at the anaerobic threshold. In conclusion, it has been shown that the WU and the two halves of the match load the body to varying degrees, the former doing so to a lesser extent than FH or SH.